TINGKAT KETERGANTUNGAN NIKOTIN DAN FAKTOR-FAKTOR YANG BERHUBUNGAN PADA PEROKOK DI DESA PENGLIPURAN 2009 - Bagus Artana, IGN; Ngurah Rai, IB (journal of internal medicine, 2010)
Smoking causes many harmful side effects to our health. Cardiac diseases, lung and respiratory problems, and almostevery malignancies had a very close relationship with cigarrete smoking. Smoking cessation is a di! cult thing to do. We haveto obtain data about nicotine dependence before starting a smoking cessation program for patients or in comunity. Nicotinedependence based on structural interview using The Fagerström Test for Nicotine Dependence (FTND) questionaire. We conducta population-based survey to ! nd out about nicotine dependence in a traditional balinese vilage, called Penglipuran. Penglipuranis one sample of traditional vilage in Bali with very tight traditional law. We found 72 smokers among 920 people in Penglipuran(7.78%) with mean age 40.67 ± 14.05 years old and almost 100% was male (only one female sample). They started to smokeat very young age (18.24 ± 3.07 years old) and take approximately 8.44 ± 6.76 cigarettes per day. We found the mean nicotinedependence level was 3.63 ± 1.41 (moderate dependence). As for factors related to nicotine dependence, we found that smokingonset, occupation, and length of smoking correlate with nicotine dependence signi! cantly (p < 0.05). While the other factors suchas age, sex, and educational level didn?t have any correlation with nicotine dependence. Our survey conclude that Penglipuransmokers had moderate nicotine dependence.